Saying No to Drugs: Fasting Protects Hematopoietic Stem Cells from Chemotherapy and Aging - Hine, Christopher (Cell Stem Cell, 2014)
Aging and chemotherapeutics damage hematopoietic stem cells (HSCs), leading to dysregulation of asymmetric division and subsequent immunosuppression and blood-related diseases. In this issue, Cheng et al. (2014) use prolonged fasting as a medical intervention to decrease IGF-1/PKA signaling and protect HSCs against chemotherapeutic toxicity and promote rejuvenation.